CAUSAL RELATIONSHIP BETWEEN MACROECONOMIC VARIABLES AND STOCK PRICES IN PAKISTAN (Jurnal Kemanusiaan, 2017)
ABSTRACT The intention of this research is to provide empirical evidence regarding causality among interest rate, inflation rate and exchange rate with stock prices in Pakistan for the period from 1990 to 2015. The findings from cointegration test indicated that there was a negative relationship of interest rate, inflation rate and exchange rate with stock prices. Granger causality test result shows unidirectional causality running from interest rate to stock prices and no causality was observed for inflation rate and exchange rate. The overall evidence proposed that equity market of Pakistan does not incorporate substantial information of interest rate, inflation rate and exchange rate in its stock prices and do not reflect the macroeconomic condition of the country.